2012
DOI: 10.1186/1471-2458-12-684
|View full text |Cite
|
Sign up to set email alerts
|

Priorities for research in child maltreatment, intimate partner violence and resilience to violence exposures: results of an international Delphi consensus development process

Abstract: BackgroundIntimate partner violence (IPV) and child maltreatment (CM) are major global public health problems. The Preventing Violence Across the Lifespan (PreVAiL) Research Network, an international group of over 60 researchers and national and international knowledge-user partners in CM and IPV, sought to identify evidence-based research priorities in IPV and CM, with a focus on resilience, using a modified Delphi consensus development process.MethodsReview of existing empirical evidence, PreVAiL documents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 26 publications
(34 reference statements)
0
48
1
1
Order By: Relevance
“…For example, The Preventing Violence Across the Lifespan (PreVAiL) Research Network, established in 2009, is an international research collaboration of over 75 researchers, trainees and knowledge users from Canada, the USA, the UK, Asia, Europe and Australia. PreVAiL members have participated in team meetings, research priority setting processes,21 research projects and mentoring of trainees. PreVAiL is an example of a non-traditional IKT model involving researchers and partners (ie, organisations comprising practitioners, policymakers and/or other types of knowledge users) that is demonstrating some promising findings in meeting the goal of research-to-action 22…”
Section: Discussionmentioning
confidence: 99%
“…For example, The Preventing Violence Across the Lifespan (PreVAiL) Research Network, established in 2009, is an international research collaboration of over 75 researchers, trainees and knowledge users from Canada, the USA, the UK, Asia, Europe and Australia. PreVAiL members have participated in team meetings, research priority setting processes,21 research projects and mentoring of trainees. PreVAiL is an example of a non-traditional IKT model involving researchers and partners (ie, organisations comprising practitioners, policymakers and/or other types of knowledge users) that is demonstrating some promising findings in meeting the goal of research-to-action 22…”
Section: Discussionmentioning
confidence: 99%
“…Three of the top five priorities identified by Wathen et al 305 identified the need to (1) examine the elements underpinning promising or successful programmes so they can serve as building blocks for intervention pilot work; (2) develop and evaluate new interventions for preventing recurrence of, or impairment associated with, exposure to child maltreatment; and (3) adapt/apply existing evidence-based child maltreatment interventions (primary and secondary prevention, for children, families and offenders), including ongoing evaluation to understand which interventions work in which settings/contexts. Our recommendations regarding best-bet programmes and outstanding research gaps help to specify these fairly general research priorities further, providing important direction for researchers, particularly in the UK.…”
Section: Comparison With Other Researchmentioning
confidence: 99%
“…304 The recent Roadmap for Mental Health Research in Europe initiative, which was set up to develop the pan-European agenda for mental health research with immediate and long-term priorities, provides a good example of cross-country collaboration to systematically address gaps in research knowledge. 72 In the DVA field, there has been significant ground broken by The Preventing Violence Across the Lifespan Research Network, 305 which was an international group of over 60 international researchers and knowledge-user partners in the field of child maltreatment and intimate partner violence (funded by the Canadian Institutes for Health Research's Institute for Gender and Health and Institute of Neurosciences, Mental Health and Addictions) brought together to develop evidence-based research priorities with regard to child maltreatment (including exposure to DVA) and intimate partner violence. The success of this collaboration is being built upon by the Violence, Evidence, Guidance, Action initiative funded by the Public Health Agency of Canada to develop national-level evidence-based public health guidance, protocols, curricula and tools for health and social service professionals.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Despite these discrepancies, the magnitude of the phenomenon is high, and efforts deserve to be made to improve this situation. The development of strategies that encourage dialogue and allow the couple to exercise a culture of peace seems to be a path in this direction 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Discussions are needed on the possible effects of these decisions on the risk and association between intimate partner violence and unfavorable outcomes for the child's and mother's health and nutrition. Recently, Wathen et al 28 stated that measurement of intimate partner violence, child abuse, and resilience to exposure to violence should be research priorities. Other authors have mentioned the quantity and quality of data produced by different scales, knowledge acquired from studies, and the practical use of this knowledge [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%